2007
DOI: 10.1021/jp072880a
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a Multimode System Coupled to Multiple Heat Baths Probed by Two-Dimensional Infrared Spectroscopy

Abstract: Reduced equation of motion for a multimode system coupled to multiple heat baths is constructed by extending the quantum Fokker-Planck equation with low-temperature correction terms (J. Phys. Soc. Jpn. 2005, 74, 3131). Unlike such common approaches used to describe intramolecular multimode vibration as a BlochRedfield theory and a stochastic theory, the present formalism is defined by the molecular coordinates. To explore the correlation among different modes through baths, we consider two cases of system-bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
109
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 61 publications
1
109
0
Order By: Relevance
“…in studies on DNA, 9, 10 and a similar mechanism has been shown to be operative for coherent vibrational excitation energy transfer in various model systems. 7,8 Scholes and coworkers 2 have suggested that in certain light harvesting complexes such as PC645 or PE545 from cryptophyte algae where the chromophores are covalently bonded to the protein backbone, this type of correlation might be larger compared to regular harvesting complexes in which the chromophores simply intercalate into the protein structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in studies on DNA, 9, 10 and a similar mechanism has been shown to be operative for coherent vibrational excitation energy transfer in various model systems. 7,8 Scholes and coworkers 2 have suggested that in certain light harvesting complexes such as PC645 or PE545 from cryptophyte algae where the chromophores are covalently bonded to the protein backbone, this type of correlation might be larger compared to regular harvesting complexes in which the chromophores simply intercalate into the protein structure.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] Detailed systembath interaction models have also been developed including a cross-coupling model 23 and the common bath coupling model. 8,9,[24][25][26] All of these studies so far incorporate the effects of correlation between fluctuations in the excitation energies of different sites. As suggested above, other possible correlations between site energy and inter-site coupling fluctuations may be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Uncorrelated baths are the default choice in many simulations, although there exist strong experimental indications that this assumption is not universally applicable [32-34, 60, 61], and partially correlated baths are more appropriate for describing coherent energy and exciton transport [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. The present analysis suggests that relaxation of molecular aggregates in the R and Q subspaces is governed by two different rates ν and ν γ .…”
Section: Discussionmentioning
confidence: 89%
“…32,43 Since HEOM approach is a dynamical theory based on the Hamiltonian, the system approaches a thermal equilibrium state at finite temperature, when the external perturbation is switched off. Thanks to the truncation schemes for higher-order hierarchy elements [44][45][46][47] one can numerically integrate HEOM for variety of systems expressed as Wigner distributions [48][49][50][51][52] and energy eigen states [53][54][55][56][57] as well as when a time-dependent external perturbation such as laser 49 or magnetic excitation 58 is present. By generalizing hierarchy structures, one can deal with a low temperature system 45,59,60 as well as general spectral distributions 61 including Brownian spectral distributions [62][63][64][65] and a Lorentzian distribution.…”
Section: Introductionmentioning
confidence: 99%